ACCOUNTING OF LAND RESOURCES IN CONDITIONS APPLICATION OF INNOVATIVE TECHNOLOGIES - Грищук, Анна (SWorldJournal, 2021)
The paper considers the role and importance of the application of innovative technologies in accounting for land resources of agricultural importance. The current state of land resources in Ukraine in comparison with the countries of the European Union i